Antioxidant role and subcellular location of hypotaurine and taurine in human neutrophils - Green, T R; Fellman, J H; Eicher, A L; Pratt, K L (Biochimica et biophysica acta, 1991)
The subcellular location of taurine, and its precursor, hypotaurine, within human neutrophils has been examined by nitrogen cavitation, Percoll-gradient centrifugation and HPLC analysis. Hypotaurine and taurine were found to reside within the cytosolic compartment of the cell. The ratio of taurine to hypotaurine is approx 50:1. The cytosolic concentration of taurine is approx. 50 mM. The concentration of hypotaurine decreased by 80% when resting neutrophils were converted into actively respiring cells by exposure to opsonized zymosan. These results prompted in vitro studies on the antioxidant properties of hypotaurine. We demonstrate by EPR spectroscopy that hypotaurine competes with 5,5'-dimethyl-1-pyrroline N-oxide) (DMPO) for hydroxyl radicals, and that it is the sulfinyl group which confers hydroxyl radical scavenging activity to it. Following its exposure to hydroxyl radicals, two oxidation products were isolated by HPLC, one of which has been identified as taurine. The biological roles of hypotaurine and taurine in the neutrophil are discussed with respect to their antioxidant properties and subcellular location within the cell.